Boron-doped few-layer graphene nanosheet gas sensor for enhanced ammonia sensing at room temperature. Issue 2 (3rd January 2020) - Srivastava, Shubhda; Jain, Shubhendra K.; Gupta, Govind; Senguttuvan, T. D.; Gupta, Bipin Kumar
Abstract : A boron-doped few-layer LPCVD graphene sensor is successfully designed and demonstrated for enhanced NH3 gas sensing applications. Abstract : Heteroatom doping in graphene is now a practiced way to alter its electronic and chemical properties to design a highly-efficient gas sensor for practical applications. In this series, here we propose boron-doped few-layer graphene for enhanced ammonia gas sensing, which could be a potential candidate for designing a sensing device. A facile approach has been used for synthesizing boron-doped few-layer graphene (BFLGr) by using a low-pressure chemical vapor deposition (LPCVD) method. Further, Raman spectroscopy has been performed to confirm the formation of graphene and XPS and FESEM characterization were carried out to validate the boron doping in the graphene lattice. To fabricate the gas sensing device, an Si/SiO2 substrate with gold patterned electrodes was used. More remarkably, the BFLGr-based sensor exhibits an extremely quick response for ammonia gas sensing with fast recovery at ambient conditions. Hence, the obtained results for the BFLGr-based gas sensor provide a new platform to design next-generation lightweight and fast gas sensing devices.